STRATEGIC MANAGEMENT ACCOUNTING - Шурпенкова, Руслана; Сарахман, Оксана; Калайтан, Татьяна (Socio-economic relations in the digital society, 2020)
The article examines the impact of strategic management decisions on an entity’s activities. Emphasis is placed on the formation of a business entity management system in a competitive environment. The role of decision-making information in each of the five interrelated processes of enterprise strategy development is defined, namely: defining the mission and setting strategic goals; analysis of the strategic position of the enterprise; formulating a strategy to achieve the defined goals and results of the activity; reviewing the strategic plan for compliance and quality; mine strategic plan or methods of its implementation. The functions, methods and systems of strategic management accounting are investigated.